Effects of different bicarbonate on spirulina in CO2 absorption and microalgae conversion hybrid system - Zhang, Pengyu; Sun, Qian; Dong, Ye; Lian, Shaohan (Frontiers in Bioengineering and Biotechnology, 2023)
According to the characteristics of power plant flue gas emission and the requirements of reducing CO2 capture cost. CO2 absorption hybrid with microalgae conversion (CAMC) can avoid the challenges of heat consumption during absorbent desorption and nutrient consumption during microalgae culture. In this study, the bicarbonate solution (represents the products of CO2 absorption by Na2CO3 and K2CO3) is used as carbon source for mutagenic Spirulina platensis cultivation, and different concentrations of bicarbonate were set to explore the best carbon source. The results showed that NaHCO3 was a better medium for the CO2 absorption hybrid with microalgae conversion system, which was beneficial for the growth of mutagenic Spirulina, compared with K2CO3. When .3 mol/L NaHCO3 was added to the CO2 absorption hybrid with microalgae conversion system, the highest biomass dry weight, carbon fixation rate and carbon utilization efficiency were obtained, which were 2.24 g/L, 230.36 mg/L/d and 26.71%, respectively. In addition, .3 mol/L NaHCO3 was conducive to protein synthesis, reaching 1,625.68 mg/L. This study provided a feasible idea for power system to achieve carbon neutrality in the future.